Monstrous Animals on Hindu Temples, with Special Reference to Khajuraho - Smith, David (Religions of South Asia, 2013)
This article discusses the role of imaginary composite animals on medieval Hindu temples, with special reference to the vyalas at Khajuraho, Madhya Pradesh. These monsters are frequently sculpted on temples in the company of women, but are scarcely mentioned in texts. They are subsequently replaced in other parts of India by images of ascetics. An attempt is made to elucidate their role and meaning, within the wider context of Indian religion and culture, by positing that they may express a, so to speak, subterranean power of sexuality.